2008
DOI: 10.1016/j.chemosphere.2007.04.090
|View full text |Cite
|
Sign up to set email alerts
|

DDT and its metabolites in breast milk from the Madeira River basin in the Amazon, Brazil

Abstract: Until the 1990's the 1,1,1-trichloro-bis-2,2′-(4chlorophenyl) ethane (DDT) was sprayed in the walls of the house in the along the Madeira River basin, Brazilian Amazon, a region well known by its large number of malaria cases. In the 1910, the relate of Oswaldo Cruz about health conditions in Madeira River region describes the presence of malaria in rates ranging until 100% of infected people in some localities. Data available in the literature points to the DDT contamination in fishes captured in Madeira Rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
1
21
1
15
Order By: Relevance
“…Interestingly, Galapagos sea lion pups exhibited DDT concentrations similar to those detected in juveniles of Hawaiian monk seals (Monachus schauinslandi) from several subpopulations in the Northwestern Hawaiian Islands (Ylitalo et al 2008). The maximum levels of DDT concentration (1,200-3,100 lg kg -1 lipid) detected in six Galapagos sea lion pups are comparable to or higher than the concentrations recently found in Amazon River dolphins (Inia geoffrensis; 1,624 lg kg -1 lipid) (Torres et al 2009) and higher than concentrations measured in human milk (370 lg kg -1 lipid) samples from the Brazilian Amazon (Azeredo et al 2008), where DDT has been widely sprayed.…”
Section: The Ddt Legacy Continuesmentioning
confidence: 92%
“…Interestingly, Galapagos sea lion pups exhibited DDT concentrations similar to those detected in juveniles of Hawaiian monk seals (Monachus schauinslandi) from several subpopulations in the Northwestern Hawaiian Islands (Ylitalo et al 2008). The maximum levels of DDT concentration (1,200-3,100 lg kg -1 lipid) detected in six Galapagos sea lion pups are comparable to or higher than the concentrations recently found in Amazon River dolphins (Inia geoffrensis; 1,624 lg kg -1 lipid) (Torres et al 2009) and higher than concentrations measured in human milk (370 lg kg -1 lipid) samples from the Brazilian Amazon (Azeredo et al 2008), where DDT has been widely sprayed.…”
Section: The Ddt Legacy Continuesmentioning
confidence: 92%
“…A large number of studies have confirmed that DDD and DDE are the normal dechlorination metabolites of DDT (Azeredo et al 2008;Wrobel et al 2009). Using GC-MSD, three compounds (p,p′-DDD, p,p′-DDE and p,p′-DDMU) were detected as dechlorination metabolites of p,p′-DDT in waterlogged soil and in soil solution, with or without Fe 2+ addition.…”
Section: Pathways For the Dechlorination Of Pp′-ddt By Sulfidementioning
confidence: 92%
“…92 Por exemplo, chegou a ser detectada a presença de DDT até no leite materno. [93][94][95][96][97][98][99][100][101] A grande polêmica movida pelo instigante e provocativo livro é que ele não só expunha os perigos do DDT, mas questionava, de forma eloquente, a confiança "cega" da humanidade no progresso tecnológico. Dessa forma, o livro ajudou a abrir espaço para o movimento ambientalista que se seguiu.…”
Section: História Dos Agrotóxicosunclassified